Comprehensive characterization of hygroscopic properties of methanesulfonates. (1st March 2020) - Guo, Liya; Peng, Chao; Zong, Taomou; Gu, Wenjun; Ma, Qingxin; Wu, Zhijun; Wang, Zhe; Ding, Xiang; Hu, Min; Wang, Xinming; Tang, Mingjin
Abstract: Methanesulfonate, formed in atmospheric oxidation of dimethyl sulfide, is abundant in marine aerosols; however, its hygroscopic properties have not been well understood. In this work, two complementary techniques (a vapor sorption analyzer and a humidity tandem differential mobility analyzer) were employed to investigate hygroscopic properties of CH3 SO3 Na, CH3 SO3 K and (CH3 SO3 )2 Ca at different relative humidities (RH). The deliquescence relative humidities were measured to be 70–71% for CH3 SO3 Na at 15–35 °C, displaying no dependence on temperature. The mass changes at 90% RH, relative to that at <1% RH, were measured to be 4.002 ± 0.053 for CH3 SO3 Na, 3.479 ± 0.031 for CH3 SO3 K, and 3.663 ± 0.019 for (CH3 SO3 )2 Ca at 25 °C. CH3 SO3 Na and CH3 SO3 K aerosols started to grow at >70% RH, while continuous growth since very low RH (<40%) was observed for (CH3 SO3 )2 Ca aerosols. At room temperature, hygroscopic growth factors at 90% RH were measured to be 1.48 ± 0.02, 1.53 ± 0.04 and 1.65 ± 0.02 for CH3 SO3 Na, CH3 SO3 K and (CH3 SO3 )2 Ca aerosols, respectively. Highlights: Hygroscopic properties of three methanesulfonates were investigated using two techniques. The mass change of CH3 SO3 Na at 90% RH, relative to that at <1% RH, was measured to be 4.0. The growth factor was measured to be 1.48 ± 0.02 at 90% RH for CH3 SO3 Na aerosol.